Experienced well-being and labor market status: The role of pleasure and meaning - Tobias Wolf; Maria Metzing; Richard E. Lucas (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper examines experienced well-being of employed and unemployed workers. We use the survey-adapted day reconstruction method (DRM) of the Innovation Sample of the German Socio-Economic Panel Study (SOEP-IS) to analyze the role of the employment status for well-being, incorporating complete time use. Summarizing the average share of pleasurable minutes, we generate the P-index. We show that - in contrast to evaluative life satisfaction - the average unemployed experiences more pleasurable minutes due to the absence of working episodes. Hence, we examine working episodes in depth. While working is among the activities with the highest propensities for an unpleasant experience, it is also among the most meaningful activities. We show that meaning is a central non-monetary determinant for a pleasurable work episode and find that pleasure during work and job satisfaction in general have the same association with meaning.
Keywords: I31; J22; J60; D91; 330; experienced well-being; time use; Unemployment; Day Reconstruction Method; DRM; SOEP-IS